The subtribes and genera of the tribe Broscini (Coleoptera: Carabidae): cladistic analysis, taxonomic treatment, and biogeographical considerations - Roig, Sergio Alberto (2000)
Phylogenetic relationships of the genera of the tribe Broscini (Carabidae) are postulated based on cladistic methods. Seventy-three morphological characters were examined in 88 species, arranged in 41 genera and subgenera, and with the related tribes Melaenini and Apotomini as outgroups. In all the obtained cladograms, the genera are grouped in five clades recognized as the basis for a new subtribal classification: the Oriental-Palearctic-Neotropical Axonyina, new subtribe (type genus, Axonya Andrewes) with 3 genera; the Holarctic-Oriental subtribe Broscina (type genus Broscus Panzer) with 9 genera; the south temperate Australian-Neotropical Nothobroscina new subtribe (type genus Nothobroscus Roig-Juñent and Ball) with 10 genera; the south temperate Neotropical Barypina (type genus Barypus Dejean) with 2 genera; and the south temperate Australian-Neotropical Creobiina (type genus Creobius Guérin-Ménéville) with 11 genera. Species groups within diverse genera Barypus, Eurylychnus Bates, and Promecoderus Dejean were treated as terminal units to test monophyly of these genera. Results of the analysis show that only Promecoderus is not monophyletic, as presently structured. Keys and diagnoses are provided for the genera of Broscini, and all taxonomically important structures are illustrated. Genital features of males and females are described for the first time for several genera. The barypine genus Microbarypus, with its type species M. silvicola (type locality Alto Queulat, Aisén, Chile) is described as new. The species Percosoma concolor Sloane, P. substriatum Moore, and P. montanum Castelnau are transferred to the genus Chylnus. Type species are designated for Adotela Castelnau (Adotela concolor Castelnau), Gnathoxys Westwood (Gnathoxys granularis Westwood), and Cerotalis Castelnau (Cerotalis substriata Castelnau). The four main biogeographical hypotheses proposed to explain Broscini distribution are discussed. Recent discovery of new Neotropical genera, as Nothobroscus Roig-Juñent and Ball and Rawlinsius Davidson and Ball, together with the phylogeny of Broscini, lead to a different biogeographic hypothesis. Broscini can be considered a Pangaeic tribe originating in Lower Jurassic times when there was a land connection between South America and North America on the Pacific margin. In broad terms, the biogeographic pattern of Broscini may be explained by the current hypothesis of the breakup of Pangaea.